Open study

is now brainly

With Brainly you can:

  • Get homework help from millions of students and moderators
  • Learn how to solve problems with step-by-step explanations
  • Share your knowledge and earn points by helping other students
  • Learn anywhere, anytime with the Brainly app!

A community for students.

Deriving kinematic equations

Physics
See more answers at brainly.com
At vero eos et accusamus et iusto odio dignissimos ducimus qui blanditiis praesentium voluptatum deleniti atque corrupti quos dolores et quas molestias excepturi sint occaecati cupiditate non provident, similique sunt in culpa qui officia deserunt mollitia animi, id est laborum et dolorum fuga. Et harum quidem rerum facilis est et expedita distinctio. Nam libero tempore, cum soluta nobis est eligendi optio cumque nihil impedit quo minus id quod maxime placeat facere possimus, omnis voluptas assumenda est, omnis dolor repellendus. Itaque earum rerum hic tenetur a sapiente delectus, ut aut reiciendis voluptatibus maiores alias consequatur aut perferendis doloribus asperiores repellat.

Join Brainly to access

this expert answer

SEE EXPERT ANSWER

To see the expert answer you'll need to create a free account at Brainly

For a = constant
\[v=\int a dt=at+c\]c = initial velocity So, \[v=u+at\]
good job

Not the answer you are looking for?

Search for more explanations.

Ask your own question

Other answers:

if a constan, a =0 v = u + at v = u + 0 v = u
\[x_f = \int v(t) dt=\int (\int a dt) dt = \int(at+u)dt = \frac{1}{2}at^2 + ut +c\], c = initial position So, \[x_f = ut +\frac{1}{2}at^2 + x_i\]\[x_f-x_i = ut +\frac{1}{2}at^2\]\[s = ut+\frac{1}{2}at^2\]s=displacement.
for a = 0; s = ut + 0.5 at^2 s = ut + 0 s = ut
From the third post, \[s=ut+\frac{1}{2}at^2\]\[at^2+2ut -2s = 0\]\[t^2 + \frac{2u}{a}t - \frac{2s}{a}=0\]\[(t+\frac{u}{a})^2 - \frac{u^2}{a^2}-\frac{2s}{a}=0\]\[(t+\frac{u}{a})^2 = \frac{u^2-2as}{a^2}\]\[t+\frac{u}{a} = \frac{\sqrt{u^2-2as}}{a}\]\[t = \frac{\sqrt{u^2-2as}-u}{a} -(1)\] Put (1) into v=u+at \[v =u+a(\frac{\sqrt{u^2-2as}-u}{a})\]\[v = u +\sqrt{u^2-2as}-u\]\[v^2 = u^2 +2as\]
\[x_f = \int v(t) dt = v_{ave}t+C\]c = initial position \[x_f = v_{ave}t +x_i\]\[x_f = \frac{1}{2}(u+v)t +x_i \]\[s = \frac{1}{2}(u+v)t\]displacement = s = \(x_f - x_i\)
Probably something wrong with the last post, which is s=(1/2) (u+v)t.
that's correct ... it assumes constant acceleration. that;s all.
Seriously?! I did it!?!
let me see how can i put it up logically.
|dw:1351833416633:dw|
now you just need to show that for constant accn V_av = (u+v)/2 ... wanna try it?
Huh!? I thought it's some maths.. Oh..How to start??
try using MVT
MVT.... again.../_\
well, you can do this without MVT ,,, i was wondering if i could improve my skills with MVT. try expanding v(t) in the expression of average.
or, V_av = s/t
expanding v(t)?
v(t) = u + at
or simply put ,,, average velocity = distance/time
Fail ._.
\[v_f= v_i+\int_0^{t_f} a dt=v_i + at\] So, \[v_f=v_i + at\]
\[x_f = x_i+\int_0^{t_f} v(t) dt= x_i+\int_0^{t_f} (v_i+at) dt = x_i+v_it+\frac{1}{2}at^2\] So, \[x_f = x_i+v_it+\frac{1}{2}at^2\] That is \[x_f - x_i = v_it+\frac{1}{2}at^2\]\[s= ut+\frac{1}{2}at^2\]
|dw:1351853269560:dw|
|dw:1351853406639:dw|

Not the answer you are looking for?

Search for more explanations.

Ask your own question